2018
DOI: 10.15678/aoc.2018.1802
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy Effects in Ukraine

Abstract: This paper empirically analyses fiscal policy effects in Ukraine using different identification strategies within the framework of a vector error correction model (VECM). For quarterly data from 2001 to 2016, we find a robust positive impact of both government expenditure and net revenue upon output in Ukraine, which closely corresponds with the predictions of the Mankiw-Summers model in the case of high demand for money in relation to consumption expenditure combined with significant investment elasticity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…When it comes to scientific research of the fiscal policy of Ukraine in the context of its impact on economic development, it is worth noting the publication of Shevchuk V. and Kopych R. (2018), in which the analysis of the effectiveness of fiscal policy in Ukraine has been conducted. The scholars have come to conclusion on the advisability of an income-based financial consolidation policy in Ukraine, forasmuch as better tax collection can contribute to economic growth even in the short term perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When it comes to scientific research of the fiscal policy of Ukraine in the context of its impact on economic development, it is worth noting the publication of Shevchuk V. and Kopych R. (2018), in which the analysis of the effectiveness of fiscal policy in Ukraine has been conducted. The scholars have come to conclusion on the advisability of an income-based financial consolidation policy in Ukraine, forasmuch as better tax collection can contribute to economic growth even in the short term perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also found out that taxation would increase the total cost of product and increase the price level but the output will be reduced due to lower income in Indonesia. Shevchuk and Kopych (2018), using vector error correction model, studied the Ukrainian fiscal policy and other variables to examine their impact on output for quarterly data for the period 2001 to 2016. They observed that government expenditure and net revenue has a strong positive relation with output but the interest rate has an inverse relationship with output.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When it comes to scientific research of the fiscal policy of Ukraine in the context of its impact on economic development, it is worth noting the publication of Shevchuk & Kopych (2018) conclude that the advisability of an income-based financial consolidation policy in Ukraine, forasmuch as better tax collection can contribute to economic growth even in the short term perspective. Grazhevskaa & Virchenkoa (2014) prove the significant dependence of the effectiveness of the mechanism of fiscal policy transfer in the Ukrainian economy on such institutional factors as public expenditure management, consumer expectations, and the level of fiscal decentralization.…”
Section: Introductionmentioning
confidence: 99%